МАГИСТРАЛ КАНАЛЛАРДАГИ СУВНИНГ БЕҚАРОР ҲАРАКАТИНИ ОПТИМАЛ БОШҚАРУВ МАСАЛАСИНИНГ МАТЕМАТИК МОДЕЛИ - Қудайбергенов, А.А. (SCIENCE and SOCIETY, 2021)
Mathematical for models, have been developed of sections of the main channel based on the nonlinear differential equations of Saint-Venant, describing the unsteady movements of the water flow in them. Also, an algorithmic sequence is given for determining the operating modes of a hydraulic structure, using which it is possible to manage the water resources of the main channel, providing the needs of water users with a minimum of losses of water and energy resources.
Keywords: open channel; main channel; channel section; flow; slope; control; differential equation; Saint-Venant equation; water flow; water level; hydraulic structure; quality criterion